Ac-Cent-Tchu-Ate the positive. Issue 2 (5th August 2014) - M. Watson, Ann
Abstract : Purpose: – The purpose of this column is to address how utilizing positive psychology can be beneficial in solving complex problems and increasing staff productivity. Design/methodology/approach: – This is a viewpoint column. Findings: – Many academic libraries, along with their parent institutions, are facing difficult challenges. Finding ways to maintain a positive outlook can be beneficial in meeting these obstacles and keeping staff motivated and productive. Originality/value: – This column addresses how the author's history of reading self-help books has been beneficial in providing leadership tools and in helping overcome challenging circumstances in academic libraries.